Report on the Second SIGIR Workshop on Neural Information Retrieval (Neu-IR'17) - Craswell, Nick; Croft, W. Bruce; Rĳke, Maarten de; Guo, Jiafeng; Mitra, Bhaskar (SIGIR Forum, 2017)
The second SIGIR workshop on neural information retrieval (Neu-IR'17) took place on August 11, 2017, in Tokyo, Japan. Following the successful 2016 edition, the workshop continued to serve as a forum for academic and industrial researchers to present new work on neural methods for retrieval. In addition, a special track was organized focusing on resources for evaluation and reproducibility, including proposals for public benchmarking datasets and shared model repositories. A total of 19 papers—which included five special track papers—were presented in the form of oral or poster presentations. Organizers of four of the TREC 2017 tracks were invited to present at the workshop on how these IR tasks may be suitable for evaluating recent data-hungry neural approaches. The full-day workshop—with more than 170 registrants—concluded with an engaging panel discussion.